The Politics of Austerity and the Conservative Offensive against US Public Sector Unions, 2008-2012 - Cantin, Étienne (Relations industrielles / Industrial Relations, 2012)
SummarySince the onset of the Great Recession, anti-union conservatives have been hammering out an arguably bogus yet politically potent argument: collective bargaining with government workers is unaffordable as their wages, health benefits, and pensions are driving states into deficits. Whilst evidence does not support the politically motivated attacks on public sector workers and their unions, a confluence of political-economic factors has been abetting efforts to scapegoat public employees and their unions.The first section of this essay places the 2011 wave of anti-public-sector-collective-bargaining statutes in its broad political and economic context. Whilst resulting from a longstanding hostility of the USA’s conservative movement to unionism and collective bargaining, recent anti-public-sector-collective-bargaining statutes are also the outcome of three political-economic developments galvanising anti-union GOPers—first, the fact that most US union members are now government workers, which makes it easier for anti-unionists to characterize them as a “privileged” elite; second, the Great Recession and ensuing deficit crisis; and third, the rousing of the conservative movement that led to the 2010 electoral “shellacking” of the Democrats. The second section focuses specifically on Wisconsin and argues that what is going on there ought to be seen for what it is: an attempt to exploit the economic crisis to win an eminently political victory over organised labour and allied Democrats.